The association between serum creatine kinase, mood and psychosis in inpatients with schizophrenia, bipolar and schizoaffective disorders. (30th April 2016) - Hollander, Sarah; Hochman, Eldar; Shoval, Gal; Taler, Michal; Trommer, Sharon; Hermesh, Haggai; Weizman, Abraham; Krivoy, Amir
Abstract: Previous studies demonstrated levels of serum CK (sCK) in the majority of patients undergoing acute psychosis. Records of 1054 patients hospitalized in Geha Mental Health Center during the study period were analyzed. Of them, 743 have been diagnosed with schizophrenia (Sz), 170 with schizoaffective disorder (SzA), and 158 with bipolar disorder (BP-I). Baseline sCK and PANSS values were obtained from each patient upon admission. Our results show that LnsCK is higher in patients with BP-I in comparison with patients with SZ, but not significantly different compared to patients with SzA. A multivariate analysis using linear regression model in which LnsCK was predicted by factors such as PANSS-total and sub-scores, IM injection, BMI, gender, and age among patients at each admission, revealed that PANSS-depression was inversely associated with LnsCK level in SzA and BP-I and not in SZ. A positive association was found between PANSS-total and sCK in SzA and BP-I; however, PANSS-positive scores correlated with sCK only in SzA. After controlling for confounders, it seems that sCK level is associated with the both affective and psychotic components. Serum CK may serve as a biomarker for affective exacerbation rather than psychosis. Highlights: Serum CK (sCK) levels correlate with the affective psychopathology component. No significant correlation was found between psychosis severity and sCK level. . Variable adjustment is needed to validate the sCK - psychopathology relationship. sCK may serve as a biomarker for affective exacerbation rather than psychosis. .